Practical Education Fostered by Research Projects in an Embedded Systems Course - Vanderlei Bonato; Marcio M. Fernandes; Joao M. P. Cardoso; Eduardo Marques (International Journal of Reconfigurable Computing)
The very nature of universities makes them unique environments for research and teaching. Although both activities constantly borrow from each other, a deeper level of interaction is not always achieved for several reasons. This paper presents a successful experience on conducting an undergraduate course on embedded systems, based on strong interaction with related research activities previously conducted by the authors. Known for being everywhere, embedded systems are constantly expanding in both complexity and volume production. In addition, heterogeneous systems are becoming prevalent in modern applications, standing as an additional difficulty to students in this area. In this context, this paper presents experiences in teaching embedded systems using a project-based learning pedagogical approach, with strong emphasis on mobile robotic applications previously developed by MSc and PhD students. As a result, it has been observed that undergraduate students have the opportunity to build a strong background and feel better prepared to face the challenges to be found in their future professional activities.